Peran Pendidikan Agama Islam dalam Pembentukan Karakter Generasi Z pada Siswa SMA Negeri 1 Rambang Niru - Yeni Yuliana (UIN Fatmawati Sukarno Bengkulu, 2025)
Education in Islam does not only emphasize teaching oriented towards intellectual reasoning, but rather emphasizes education that leads to the formation of personality, in other words, education is one of the main elements in the formation of the next generation of the nation who can carry out community affairs in the future. Islamic religious education does not only make children intelligent in intellect, but also intelligent in character. Generation Z are children born around 1995 to 2010. They prefer to interact with online systems, so they do not meet their friends. Generation Z has a characteristic where the internet has developed rapidly along with the development of electronic and digital media. This research is a qualitative research type, taking the background of SMA N1 Rambang Niru. Determination of the object in this study used purposive sampling and snowball sampling techniques. Data collection was carried out by conducting observations, interviews and documentation with research subjects PAI Teachers, and Students of SMA N1 Rambang Niru. The analysis was carried out by reducing data, presenting data, then drawing conclusions. The data collection procedure in this study used three techniques: a) Participant Observation, b) In-depth interviews, c) Documentation. Meanwhile, data validity was carried out through data verification, namely by checking the research methodology used to obtain the data and examining the final report.